(untitled) (Boletín de la Sociedad Zoológica del Uruguay, 2025)
The “boga” (Megaleporinus obtusidens) is a fish of great importance in both fisheries and ecology in the Uruguay River with wide phenotypic plasticity and variation in its body morphology. Despite this, little is known about its biology and reproductive ecology. In this study, we evaluate the reproductive dynamics of M. obtusidens with contrasting morphologies in the lower Uruguay River. The fish were collected monthly during two years, identifying the morphotype as Morphotype 1 ("elongated body”) or Morphotype 2 (“oval body”) (n=232). Traditional and Geometric Morphometry was used in a subset of specimens to test for morphological differences. Likewise the Gonadosomatic Index (GSI) was estimated and compared between Morphotype 1 and Morphotype 2. Morphometric analysis confirmed the differences between contrasting morphotypes. The two morphs exhibited distinct reproductive patterns: the individuals of Morphotype 2 recorded higher GSI in spring, marking a reproductive peak in November, while the specimens of Morphotype 1 showed no differences in GSI between seasons. This study shows that there are two morphs of M. obtusidens found in lower Uruguay River which may represent two different taxonomic units or perhaps two stocks. This should be considered in fisheries management, to attain a more sustainable use of this resource.